The Dynamic of Social Relations and Conflicts in Mining Area in Indonesia Study of Mining in Bahodopi of Marowali, Central Sulawesi (Komunitas, 2020)
The study of socio-cultural institutions related to natural resource management includes two factors namely IPSO facto (based on facts) namely management in an area marked by the presence of people who carry out activities and IPSO de jure (based on law) namely management based on legal aspects positive. This article aims to analyze how the socio-cultural principles lived by the community in Bahodopi District, Morowali Regency in response to their lives. The results showed that the dynamics of community life after the entry of the mine in Bahodopi had broad implications related to social life. However, empirically, this study shows that the conflict mechanism that arises is more dominated by conflicts between migrants and local residents, as well as local communities and companies. The number of conflicts raised by the community is a low escalation but has a broad impact on the sustainability and existence of investment management. The interaction of various cultures that have different perspectives is typical even though it has the potential to create conflict and even violence if it is not appropriately managed. Socio-cultural background with a different basis is a trigger for disharmony in the community if it cannot be appropriately managed. The conflict that occurs mainly with the appearance of two ethnic entities facing each other is an irony in the life of a capitalistic character.